Development of Power Management on Unmanned Surface Vehicles to Measure Battery Voltage and Power - Alia, Diana; Nurdiansari, Henna; Gupron, Akhmad Kasan; Siregar, Amelia Greacy Talenta (Universitas Negeri Malang, 2025)
This research focuses on designing an electrical system for unmanned surface vehicles (USV) to ensure optimal performance during survey operations. This USV ship is a catamaran-type ship with a Sonar Deeper depth sensor to know the depth of the water and is equipped with long range (LoRa) as a data transmitter. The USV electrical system design incorporates the use of a 4050 mAh 11.1 V LiPo battery and an iMAX B6AC charger, with evaluations covering battery charging, power consumption, and voltage stability. The trials showed that the battery supported the operation of the USV for approximately 47.8 minutes at a power load of 45.08 Watts. Battery charging showed two main phases: constant current and constant voltage, with a full charge time of approximately 2.7 hours. During operation, voltage consumption showed significant fluctuations, highlighting the need for an electrical system design that maintains voltage stability to improve performance. From the test results, the battery efficiency was found to be 91.29%. These findings emphasize the importance of appropriate component selection and efficient power management to achieve reliable and efficient USV operation. With a deep understanding of the charging characteristics and power consumption, the designed electrical system can ensure more stable USV operation and better performance under various survey conditions.